Control of Geological Structure on the Springs Distribution and Their Physical Properties. Case Study: Southern Slope of Mt. Lampobattang, South Sulawesi - MAHENDRA, GALIH AJI; Waliana Muda Iskandarsyah, Teuku Yan; ismawan, Ismawan ismawan; Brilian, Ciria Humanis (Journal of Geological Sciences and Applied Geology, 2019)
The study area is located at Southern Slope of Mt. Lampobattang, South Sulawesi. According to Armstrong (2012), Sulawesi is controlled by a complex geological structure. This condition can affect the characteristics of subsurface groundwater (Ismawan, 2013) specifically on the distribution and physical properties of springs. So, this research is needed to do. The aim of this study is to know the effect of geological structure on the distribution and physical properties of springs in the study area. This research was conducted with a qualitative analysis method of field data which resulted by geological and hydrogeological mapping at the study area. Based on the analysis results, the study area is consisted of 7 rock units consist of tuff, breccia and lava. There are 6 faults that control the study area with SW-NE and SE-NW trend. The study area is divided into 3 fracture density zones, those are low fracture density (0-500 M-1), medium fracture density (500-950 M-1), and high fracture density (950-1200 M-1). The geological structure affects the distribution of springs and their physical characteristics. This is evidenced by the appearance of springs along the fault and in the medium to high density zone. The characteristics of the Physical Properties of springs are influenced by the occurrence of faults and fractures in the study area that make the low values of EC and TDS. TDS values of springs have a vulnerable value of 0-193 ppm and EC values 0-357 μS. Therefore, the fracture and fault as the geological structure affect the distribution and physical properties of springs in the study area.